METASTATIC CUTANEOUS PLASMOCYTOMA IN A PATIENT WITH MULTIPLE MYELOMA - Neide Pereira; Ana Brinca; Óscar Tellechea; Margarida Gonçalo (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Introduction: In multiple myeloma, the cutaneous lesions are rare and usually occur in late stages of MM as a reflection of increased tumour cell burden. Case report: The authors present the case of a 66 year-old woman with IgG lambda multiple myeloma that, after 16 months and apparently under control haematological, developed a tender and firm erythemato-violaceous plaque, on the back of the right thigh. A diagnosis of cutaneous plasmocytoma was confirmed by skin biopsy. Local radiotherapy induced a complete regression of skin lesion, but the patient died 4 months later, duo to uncontrolled multiple myeloma. Discussion: Secondary cutaneous plasmocytoma usually arise from direct spread from underlying bone, manifest as erythematous to violaceous infiltrated nodules or plaques, are extremely rare and indicate a poor prognosis, as in our case. The presentation as an erysipela-like lesion with no underlying bone disease is even rarer.KEYWORDS – Multiple myeloma; Plasmacytoma; Skin neoplasms/secondary.